Improving Student Activities and Learning Outcomes Through the Problem based Learning (PBL) Model in Geography Learning - Nada Nilam Suri; Yurni Suasti; Ernawati Ernawati (Postgraduate School, Universitas Negeri Padang, 2022)
The purpose of the study is to determine the application of the Problem Based Learning (PBL) model, student activities during the application, and student learning outcomes after the application of the Problem Based Learning (PBL) model to geography learning. This research is Classroom Action Research (PTK) or Classroom Action Research (CAR). Steps for implementing actions in PTK with action planning, action implementation, observation, and reflection.Data collection techniques with observations, scales, and tests. Based on the results of this study, it was found that this study student activity while applying the PBL learning model to exponential and logarithmic material in class X IPS 1 SMAN 3 Bukittinggi were classified as active student criteria and student learning outcomes after applying the PBL learning model achieved classical completion of 87.5%.